Field emission of doped carbon nanotubes - Ahn, HS; Lee, KR; Kim, DY; Han, SW (AMER INST PHYSICS, 2006)
We calculated field-emission currents from nitrogen- and boron-doped single-walled (5,5) carbon nanotubes by integrating time-dependent Schrodinger equations. Nitrogen doping increased the emission current owing to a shift in the energy level of a localized state to the Fermi level, and the creation of coupled states that have characteristics of both localized and extended states. On the other hand, boron doping had an opposite effect on the electronic structure by increasing the energy level of the localized state. The calculated emission currents of the boron-doped carbon nanotube fluctuated depending on the doping site and the external electric field. (c) 2006 American Institute of Physics.
Keywords: ELECTRONIC STATES; MORPHOLOGY; GROWTH; ATOMS